Thematic, Programmatic and Methodological Approaches of the Annual Publication - Sinopoli, Franca; Subrizi, Carla; Combi, Mariella (Transnational 20th Century. Literatures, arts and cultures, 2017)
Novecento Transnazionale (Transnational 20th Century) is an academic annual journal aimed at proposing a theoretical and critical stance on key aspects of 20th century culture and history. This theoretical perspective will not consider historical processes and practices as proceeding in a one-directional perspective, following a single path, but as multiple, complex and interrelated movements. The term “transnational” indicates that contemporary modern cultural structures cannot be related to those of traditional cultures founded on geographical and language-specific contexts. Transnational knowledge takes a special interest in the processes of delocalisation – and therefore in the transnationality of cultural expression, which has become increasingly evident as a result of migratory movements and new communication technologies.